Karakteristik Petrografi Batupasir Formasi Sangkarewang Daerah Talawi, Kota Sawahlunto, Sumatera Barat - Ahmad Hafiz Nurmansyah; Budhi Setiawan; Yogie Zulkurnia Rochmana (Mataram University, 2026)
The Sangkarewang Formation is one of the Paleogene sedimentary units within the Ombilin Basin that developed in a lacustrine depositional system. Previous studies of the Sangkarewang Formation have mainly focused on stratigraphy, organic geochemistry, and depositional environment interpretation, while detailed investigations of the petrographic characteristics of its sandstone facies remain limited. This study aims to identify the petrographic characteristics of Sangkarewang Formation sandstones based on texture, mineral composition, porosity type, and sandstone classification. Three representative sandstone samples (BPSRG-01, BPSRG-02, and BPSRG-03) were analyzed using thin-section petrography under a polarizing microscope. The results show that the sandstones consist of very fine- to coarse-grained sediments with poor sorting and angular to sub-angular grains. The mineral composition is dominated by quartz, feldspar, and volcanic lithic fragments, indicating a contribution from volcanic-derived materials. Based on sandstone classification, samples BPSRG-01 and BPSRG-03 are classified as Arkosic Arenite, whereas BPSRG-02 is categorized as Feldspathic Wacke due to its higher matrix content. Intergranular porosity is observed in all samples, with variations controlled by grain packing and matrix abundance. These characteristics indicate that the Sangkarewang Formation sandstones were derived from relatively proximal sediment sources and experienced variations in sediment supply and depositional energy within a dynamic lacustrine system.